Intermittent Fasting: Unveiling the Therapeutic Potential in Metabolic Health Management - A Literature Review - Aqila, Fitri; Santoso, Alexander Halim (Universitas Pahlawan Tuanku Tambusai, 2024)
With the global prevalence of obesity and metabolic syndrome increasing, innovative therapeutic strategies are needed to reduce this prevalence. One approach being explored is Intermittent Fasting. This study aims to evaluate the effectiveness of Intermittent Fasting in managing Metabolic Syndrome, obesity, type 2 diabetes mellitus (T2DM), and cardiovascular risk factors. Literature searches were conducted for the period from 2010 to 2023. The analysis focused on randomized controlled trials, clinical studies, case reports, case series, and review articles assessing the effects of Intermittent Fasting on metabolic syndrome. It was found that Intermittent Fasting contributes to weight loss, improved insulin sensitivity, and modulation of leptin and adiponectin levels. Although some studies show results similar to traditional calorie restriction, Intermittent Fasting has shown potential in improving lipid profiles and reducing blood pressure. Despite its promising potential, the implementation of Intermittent Fasting in clinical practice requires a deeper understanding of its mechanisms. Furthermore, additional research is needed to evaluate the feasibility of adopting Intermittent Fasting as a lifestyle. Intermittent Fasting shows benefits in managing obesity, metabolic syndrome, and cardiovascular risk factors.